Short-term rentals and the rentier growth coalition in Pollença (Majorca). (October 2021) - Müller, Nora; Murray, Ivan; Blázquez-Salom, Macià
Since the beginning of the 2008 economic crisis, Majorca has experienced an increase in tourism, which has been made possible partly by the expansion of short-term renting. Research on short-term rentals is a growing field in critical urban and tourism geographies. This paper contributes to these fields by examining the structure of actors involved in the development of short-term rentals and their power relations. Our case study focuses on the municipality of Pollença (Majorca, Spain). Pollença was chosen due to its status as one of the most noteworthy airbnbificated places in Europe and because of the number of holiday rentals in the municipality's rural areas. While a great deal of research has focused on rent gaps and gentrification caused by short-term rentals in cities, the rentier coalition associated with short-term rentals has been comparatively overlooked. We address who the rentiers of short-term rentals are, the power relations that lie behind short-term rentals, and how these rentiers form part of a locally based coalition that has the ability to adapt planning regulations to suit their own interests. We used mixed methods, including quantitative spatial analysis and qualitative analysis in the form of interviews with those who benefit locally from short-term rentals. Our qualitative approach further included in-depth fieldwork and activist research. We conclude that a powerful rentier growth coalition has corrupted democracy because the regulatory framework has been adjusted to satisfy their interests and the conversion of properties into holiday rentals has been done either illegally or on the verge of legality without strong legal consequences.